2022
DOI: 10.3389/fendo.2022.827724
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor Function: Impact on the Human Endometrium

Abstract: The physiological role of estrogen in the female endometrium is well established. On the basis of responses to steroid hormones (progesterone, androgen, and estrogen), the endometrium is considered to have proliferative and secretory phases. Estrogen can act in the endometrium by interacting with estrogen receptors (ERs) to induce mucosal proliferation during the proliferative phase and progesterone receptor (PR) synthesis, which prepare the endometrium for the secretory phase. Mouse knockout studies have show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
78
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(81 citation statements)
references
References 164 publications
(176 reference statements)
0
78
0
3
Order By: Relevance
“…Estradiol is the most important form of estrogen, responsible for the regulation of female characteristics, the maturation of accessory sex organs, the menstruation-ovulation cycle, and the production of the mammary duct system ( 50 ). Serum concentrations of estrogens such as estradiol vary periodically throughout the menstrual cycle, with estradiol being the most abundant estrogen in females of childbearing age, except in the early follicular phase ( 51 ).…”
Section: Sex Hormones In Liver Diseasesmentioning
confidence: 99%
“…Estradiol is the most important form of estrogen, responsible for the regulation of female characteristics, the maturation of accessory sex organs, the menstruation-ovulation cycle, and the production of the mammary duct system ( 50 ). Serum concentrations of estrogens such as estradiol vary periodically throughout the menstrual cycle, with estradiol being the most abundant estrogen in females of childbearing age, except in the early follicular phase ( 51 ).…”
Section: Sex Hormones In Liver Diseasesmentioning
confidence: 99%
“…It may also be indicated that ERα and ERβ regulate processes connected with the female reproductive system in regulating several other physiological and pathophysiological processes in the human body. Disrupted ER signaling leads to the development of different diseases, such as osteoporosis, neurodegeneration, inflammation and metabolic and cardiovascular diseases [ 19 ]; however, the most important indications to modify their activity connected with estrogen-related cancers such as breast [ 19 ], endometrial [ 20 ], cervical [ 21 ] and ovarian cancer [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…The role of ERβ and its variants in cancerogenesis, breast cancer progression and prognosis response to therapy is even more complex and not fully understood despite it being over 25 years since its discovery. It seems evident that understanding is crucial for the further design of diagnostic and therapeutic strategies not only for breast and endometrial cancer [ 20 , 23 ]. Although we know relatively the most about the effect of ERβ on these cancers, the situation seems much more complicated than in the case of ERα.…”
Section: Resultsmentioning
confidence: 99%
“…In vivo study has shown that ER including ESR1, ESR2 and G protein-coupled estrogen receptor (GPER) is essential for a normal menstrual cycle. Incorrect expression of ERs can cause EC, ESR1 promotes uterine cell proliferation and increased the risk of EC, while ESR2 has the opposite effects (22). Other research has shown that LINC01541 inhibits VEGFA expression in endometrial stromal cells and that E2 stimulation significantly inhibits the expression of LINC01541, whereas overexpression of LINC01541 attenuates the migration and invasion of endometrial stromal cells induced by E2 (8).…”
Section: Discussionmentioning
confidence: 99%